2021
DOI: 10.1029/2021gl093700
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Imprints of Stratospheric Contributions to Interhemispheric Differences in Tropospheric CFC‐11, CFC‐12, and N2O Abundances

Abstract: Understanding global emissions of long-lived trace gases requires careful interpretation of in situ measurements. Emissions can be inferred from observed changes in atmospheric mole fractions along with an assumed atmospheric lifetime (WMO, 2003(WMO, , 2018. However, sparse networks of in situ trace gas measurements together with large uncertainties in atmospheric lifetimes (Ko et al., 2013) can lead to large uncertainties in inferred emissions (Lickley, 2021). Experts have long looked to hemispheric differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…We find that it is at most weakly correlated with the Brewer‐Dobson Circulation and the QBO indices that characterize the variations in the STE. In contrast, the inter‐annual growth rate anomalies of N 2 O, which has shown in previous studies to be controlled by the STE (Lickley et al., 2021; Nevison et al., 2004, 2011; Ray et al., 2020), have significant correlations with these indices. This result is consistent with the fact that the tropospheric sources and sinks play an important role for CH 4 , compared to N 2 O, but does not indicate that the contribution of the stratosphere‐troposphere CH 4 flux is negligible in all cases.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…We find that it is at most weakly correlated with the Brewer‐Dobson Circulation and the QBO indices that characterize the variations in the STE. In contrast, the inter‐annual growth rate anomalies of N 2 O, which has shown in previous studies to be controlled by the STE (Lickley et al., 2021; Nevison et al., 2004, 2011; Ray et al., 2020), have significant correlations with these indices. This result is consistent with the fact that the tropospheric sources and sinks play an important role for CH 4 , compared to N 2 O, but does not indicate that the contribution of the stratosphere‐troposphere CH 4 flux is negligible in all cases.…”
Section: Discussionmentioning
confidence: 66%
“…Previous studies have demonstrated that the FStrue→T ${F}_{S\to T}$ term has a considerable impact on the tropospheric concentrations of N 2 O, another well‐mixed greenhouse gas, at seasonal and inter‐annual scales (Lickley et al., 2021; Nevison et al., 2004, 2011; Ray et al., 2020; Ruiz et al., 2021; Ruiz & Prather, 2022; Thompson et al., 2013). Driven by the global‐scale Brewer‐Dobson circulation, N 2 O‐rich tropospheric air enters the stratosphere (where N 2 O is destroyed by photochemistry) in the tropics, and N 2 O‐depleted stratospheric air returns to the troposphere in the extra‐tropics, leading to a net troposphere‐to‐stratosphere N 2 O flux (FStrue→T ${F}_{S\to T}$ < 0) (Ruiz et al., 2021).…”
Section: Introductionmentioning
confidence: 99%